Effect of Attapulgite on the Oral Bioavailability of Ciprofloxacin - Izzah, Zamrotul; Gratia, Veronica; Aryani, Toetik; Suharjono, Suharjono (Indonesian Journal of Clinical Pharmacy, 2013)
As a result, this drug-drug interaction may reduce ciprofloxacin bioavailability. This study was aimed to determine the effect of attapulgite on the bioavailability of a single orally-administered ciprofloxacin. Six New Zealand white rabbits received each of the following treatments in a randomized, three-way crossover sequence, separated by a 7-day washout period: (i) ciprofloxacin (23 mg/kgBW) alone; (ii) ciprofloxacin (23 mg/kgBW) given simultaneously with attapulgite (28 mg/kgBW); (iii) ciprofloxacin(23 mg/kgBW) given 2 hours after attapulgite (28 mg/kgBW). Blood samples (1 mL) were collected from the marginal ear vein up to 240 minutes postdose. The plasma concentrations of ciprofloxacin were determined by a validated high-performance liquid chromatography method. The maximum concentration and oral bioavailability (AUC0-240 min) of ciprofloxacin were significantly decreased by 49% and 32% when administered concomitantly with attapulgite (p<0.001). Attapulgite appeared to have no significant effect on the bioavailability of ciprofloxacin when administered 2 hours before ciprofloxacin. In conclusion, the oral bioavailability of ciprofloxacin is markedly reduced when administered concomitantly with attapulgite. This drug-drug interaction may decrease clinical efficacy and promote microbial resistance to ciprofloxacin. However, the interaction could be minimized by separating the adminsitration of these drugs at least 2 hours.Key words: Attapulgite, bioavailability, ciprofloxacin, drug-drug interactionPengaruh Atapulgit pada Ketersediaan Hayati Siprofloksasin OralKemampuan absorpsi atapulgit dapat menghambat absorpsi siprofloksasin pada pemberian per oral. Sebagai hasilnya, interaksi obat-obat ini dapat menurunkan ketersediaan hayatiÂ siprofloksasin. Penelitian ini bertujuan untukÂ  mendeterminasi efek atapulgit pada ketersediaan hayati obat siprofloksasin yang diberikan secara oral. Sebanyak 7 kelinci putih Selandia Baru menerima perlakuan secara random dengan desain three-way crossover sequence, yang dipisahkan dengan periode washout 7 hari. (i) siprofloksasin (23 mg/kgBB); (ii) siprofloksasin (23 mg/kgBB) diberikan secara simultan dengan atapulgit (28 mg/kgBB); (iii) siprofloksasin (23 mg/kgBB) diberikan 2 jam setelah pemberian atapulgit (28 mg/kgBB. Sampel darah (1 mL) dikumpulkan pada marginal ear vein setelah 240 menit pemberian obat. Konsentrasi siprofloksasin plasma dihitung dengan metode kromatografi cair kinerja tinggi tervalidasi. Konsentrasi maksimum dan ketersediaan hayati oral (AUC0-240 min) siprofloksasin secara signifikan berkurang 49% dan 32% ketika dikombinasikan bersamaan dengan atapulgit (p< 0,001). Atapulgit tidak memiliki pengaruh signifikan pada ketersediaan hayati ketika diberikan 2 jam sebelum siprofloksasin. Ketersediaan hayati siprofloksasin berkurang secara signifikan ketika diberikan bersamaan dengan pemberian atapulgit. Interaksi obat dengan obat ini dapat mengurangi efikasi obat dan meningkatkan resistensi mikrob terhadap siprofloksasin. Namun, interaksi dapat dikurangi dengan pemberian obat pada jarak waktu minimal 2 jam.Kata kunci: Atapulgit, interaksi obat dengan obat, ketersediaan hayati, siprofloksasin